Stability and robustness of InAlGaN/GaN HEMT in short-term DC tests for different passivation schemes. (September 2018) - Oualli, M.; Dua, C.; Patard, O.; Altuntas, P.; Piotrowicz, S.; Gamarra, P.; Lacam, C.; Jacquet, J.-C.; Teisseire, L.; Lancereau, D.; Chartier, E.; Potier, C.; et al.
Abstract: On-wafer short term step-stress tests were carried out to evaluate InAlGaN/GaN HEMT devices. Three types of transistor were studied, each one having a specific two dielectric layer passivation. The results of these tests demonstrate that the upper layer of the passivation has a strong impact on the ageing of the devices. When the upper layer is an Al2 O3 Atomic Layer Deposited one, the transistors show a better stability of their electrical parameters than those passivated with the other stacks.